Construction Practice of a Dual-Dimensional Curriculum on Labor and Mental Health in Heilongjiang Province's Study and Practice Education Base Camp - Chunjin Shao (Education Research on Study Tours and Practice, 2026)
Research and Practice Education Bases and Camps serve as the core platforms for integrating school-based and extracurricular collaborative education, as well as deepening the synergy between labor education and mental health education. These two entities complement each other in function and differ in their operational formats. Leveraging Heilongjiang Province's distinctive resources—such as cold-region black soil, ice and snow ecology, red heritage, modern agriculture, national defense technology, and intangible cultural heritage—the province adopts a dual approach of specialized practical training at provincial-level research and practice education bases and immersive experiential activities at camps. This model embeds the cultivation of labor habits and mental health development throughout the entire research and practice education process, forming a dual-dimensional curriculum practice framework with Heilongjiang's distinctive identity—specialized empowerment through bases and immersive nurturing through camps. This study, grounded in the national policy orientation of integrating five types of education, aligns with Heilongjiang's requirements for fostering labor habits and "mental health safeguarding" education. By analyzing the contextual differences between research and practice education bases and camps, it elucidates the practical logic, localized paradigms, and implementation pathways for integrating labor and mental health dimensions. Supported by real-world cases from provincial-level bases and camps, it presents practical outcomes, offering a reference for enhancing the quality and effectiveness of research and practice education across the province while promoting students' physical and mental development.